Multicenter study of levodopa carbidopa intestinal gel in Parkinson's disease: the Turkish experience - (:unkn) unknown (TUBITAK SCIENTIFIC & TECHNICAL RESEARCH COUNCIL TURKEY, 2020)
Background/aim: Our purpose was to determine the efficacy of levodopa carbidopa intestinal gel (LCIG) in a series of Turkish patients with Parkinson's disease (PD). Materials and methods: We had telephone calls with 54 patients from 11 neurology centers who were on LCIG treatment, and 44 patients or their caregivers were included in an eight-item survey between September 2015 and June 2016. The reliability and validity of the survey were evaluated with intraclass correlation coefficients for every question separately. Results: Average age of the patients were 63.48 and the duration of PD was 12.79 years. Average LCIG treatment period was 15.63 months. Percentages of the patients who reported they were 'better' after LCIG treatment were as follows: 80% for time spent off, 55% for dyskinesia, 65% for tremor, 85% for gait disorder, 50% for pain, 50% for sleep disorders, 42.5% for depression, 32.5% for incontinence, and 70% for activities of daily living. Cronbach's alpha was 0.795 and the intraclass correlation coefficient was reliable for the items. Conclusion: As detected by a survey performed by telephone calls with good interrater reliability, patients with PD improve with LCIG treatment in many aspects of the disease.
Keywords: Parkinson's disease; levodopa carbidopa intestinal gel; efficacy; LONG-TERM; OPEN-LABEL; MOTOR COMPLICATIONS; NONMOTOR SYMPTOMS; DOUBLE-BLIND; INFUSION; 12-MONTH; THERAPY; SAFETY